2018
DOI: 10.1016/j.molcel.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Gene-to-Phenotype Arrays: A High-Throughput Technique for Molecular Phenotyping

Abstract: We have developed a highly parallel strategy, systematic gene-to-phenotype arrays (SGPAs), to comprehensively map the genetic landscape driving molecular phenotypes of interest. By this approach, a complete yeast genetic mutant array is crossed with fluorescent reporters and imaged on membranes at high density and contrast. Importantly, SGPA enables quantification of phenotypes that are not readily detectable in ordinary genetic analysis of cell fitness. We benchmark SGPA by examining two fundamental biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…The SUS-GFP query strain was crossed with the SPOCK collection, consisting of 5,808 yeast non-essential null and essential DaMP gene mutants (Jaeger, Ornelas et al, 2017). All library manipulations including selection of diploids, sporulation, and selection of haploids were done using standard EMAP technology (Collins et al, 2010) using a RoToR pinning robot (Singer Instruments, Taunton, UK) and Uracil and G418 selection.…”
Section: Stars Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SUS-GFP query strain was crossed with the SPOCK collection, consisting of 5,808 yeast non-essential null and essential DaMP gene mutants (Jaeger, Ornelas et al, 2017). All library manipulations including selection of diploids, sporulation, and selection of haploids were done using standard EMAP technology (Collins et al, 2010) using a RoToR pinning robot (Singer Instruments, Taunton, UK) and Uracil and G418 selection.…”
Section: Stars Methodsmentioning
confidence: 99%
“…(Carvalho et al, 2010; Garza et al, 2009; Hampton and Sommer, 2012; Nakatsukasa et al, 2016; Plemper et al, 1997; Scott and Schekman, 2008; Wahlman et al, 2007). We employed a previously characterized self-ubiquitinating substrate SUS, that undergoes retrotranslocation independent of all known candidates, along with a new complete mutant array called SPOCK (Single Plate Orf Compendium Kit), to discover mutants with deficiencies in ERAD-M retrotranslocation (Jaeger, Ornelas et al, 2017). Our analysis revealed that the derlin Dfm1 had a broad and strong role in ERAD-M in both the HRD and DOA pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier work demonstrated that Hrd1 is dispensable for the full retrotranslocation of a self-ubiquitinating substrate (SUS), which allowed for the possibility of a Hrd1-independent route out of the ER membrane for actual ERAD-M substrates ( Garza et al., 2009a ). Going forward with this idea, we employed SUS-GFP to screen the complete collection of yeast mutants with the Single Plate Orf Compendium Kit (SPOCK) array, consisting of a 5,808 yeast strain array of non-essential gene deletion mutants and essential DAmP gene mutants ( Jaeger et al., 2018 ; Neal et al., 2018 ). This work led to our identification of Dfm1 as an independent, dedicated, and specific mediator for retrotranslocating ERAD-M substrates including those from both the HRD and DOA pathways, and Hrd1 itself in circumstances when it is rapidly degraded by self-ubiquitination ( Neal et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro and structural studies by Rapoport and colleagues suggested that the multi-spanning yeast E3 ligase Hrd1 serves as a channel for luminal substrates [37][38][39]. An analogous channel for ERAD membrane substrates remained to be determined until Neal and colleagues improved the understanding of membrane substrate retrotranslocation by screening a complete collection of yeast mutants via SPOCK (single plate orf compendium kit), which consists of 5,808 yeast strain array of non-essential gene deletion mutants and essential DAmP gene mutants [49] and identified yeast derlin Dfm1 as an independent, dedicated and specific mediator for the retrotranslocation of many ERAD membrane substrates (Fig. 1) [36].…”
Section: The Underlying Role In Erad and Retrotranslocation-maintainingmentioning
confidence: 99%